2022
DOI: 10.1371/journal.pone.0262143
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of in situ analyses for the characterisation of red pigments in rock paintings: A case study from El Castillo, Spain

Abstract: Paint technology, namely paint preparation and application procedures, is an important aspect of painting traditions. With the expansion of archaeometric studies and in situ non-destructive analytical methods, a renewal of technological studies is being observed in rock art. In situ analyses have several limitations that are widely discussed in the literature, however. It is not yet clear whether they provide accurate information on paint technology, except under certain conditions. Here, we evaluated digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
(172 reference statements)
1
6
0
Order By: Relevance
“…The latter are chiefly connected to the unintentional analysis of underlying strata below paintings. This problem has been pointed out by many researchers in the study of pottery and other archaeological materials using portable XRF (Chanteraud et al, 2021;Dayet et al, 2022) and could be reinforced by our work. As has been noted, readings performed in painting motifs also contain signals of pastes and slips.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The latter are chiefly connected to the unintentional analysis of underlying strata below paintings. This problem has been pointed out by many researchers in the study of pottery and other archaeological materials using portable XRF (Chanteraud et al, 2021;Dayet et al, 2022) and could be reinforced by our work. As has been noted, readings performed in painting motifs also contain signals of pastes and slips.…”
Section: Discussionsupporting
confidence: 65%
“…Another depth of data interpretation could be reached by statistical processing of XRF results. Among different types of unsupervised data analyses, principal components analysis (PCA) is one of most used in non‐invasive XRF studies (Chanteraud et al, 2021; Dayet et al, 2022). As can be seen from Figure 2 (a), the exploratory analysis of white‐coloured pottery does not show clear clustering of any particular style.…”
Section: Resultsmentioning
confidence: 99%
“…The most applied devices are portable XRF (pXRF) and Raman. Portable XRF can read elements heavier than Al or Si; it is, therefore, possible to identify pigments in rock art palettes such as Fe from red hematite ochre and Mn in black manganese oxides [103]. Raman identifies both minerals and organic substances but encounters difficulties when identifying organic binders in situ due to fluorescent background materials; moreover, the possible diagenesis of organics may hamper the possibility to distinguish between primary constituents and neoformations.…”
Section: Methods For Investigation Of Rock Artmentioning
confidence: 99%
“…Microsamples also offer the opportunity to conduct laboratory experiments on rock substrate stability after artificial aging [147]. In a recent experiment with pXRF, Dayet et al (2022) [103] observed that the heterogeneity of paintings systems and the variability in primary and secondary minerals hamper the possibility of investigating rock art only following a non-invasive approach and concluded that the best solution for rock art research is a combination of in situ and laboratory analyses. From this perspective, a micro-invasive approach that guarantees rock art preservation and makes available a small quantity of pigments and/or rock substrate is mandatory.…”
Section: Non-invasive or Micro-invasive Methods?mentioning
confidence: 99%
“…Whether or not the mineral mixtures identified are natural or intentionally made by the artists is not yet proven. Other researchers have already discussed that different paint mixtures could either represent different paint recipes, or natural formations from similar or different raw material sources [ 42 ].…”
Section: Resultsmentioning
confidence: 99%